2014
DOI: 10.1515/jcc-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Daring Greatly: How the Courage to Be Vulnerable Transforms the Way We Live, Love, Parent, and Lead

Abstract: Author Brené Brown is not only a best-selling popular author, but also a research professor at the University of Houston Graduate College of Social Work. This review examines the perspectives and findings she presents in Daring Greatly, summarizes the research method that led her to these findings, and discusses the potential utility of this book in the college student context. http://journals.naspa.org/jcc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…The themes were generated inductively and were compared and collapsed until the surviving themes offered a problem to explore. As research professor Brené Brown (2012) pointed out, researchers should not come with a problem or a hypothesis or a literature review when employing grounded research. They should come with a topic and let the participants define the problem.…”
Section: Methodsmentioning
confidence: 99%
“…The themes were generated inductively and were compared and collapsed until the surviving themes offered a problem to explore. As research professor Brené Brown (2012) pointed out, researchers should not come with a problem or a hypothesis or a literature review when employing grounded research. They should come with a topic and let the participants define the problem.…”
Section: Methodsmentioning
confidence: 99%
“…True belonging never asks us to change who we are, it demands that we be who we are. (Brown, 2013) The research revealed that PHCPs would like to have a sense of belonging individually, socially, and institutionally.…”
Section: Brené Brown Saidmentioning
confidence: 99%
“…Most institutions in the United States do not contain the infrastructure to support leaning into vulnerability (Brown, 2012;Brown, 2018). Employee reviews that rely heavily on productivity measures, for example, structurally create and uphold a workplace culture that privileges perfectionism, hyper productivity, and inertia over risk, failure, and growth; and comparison, blame, and competition over connection, empathy, and collaboration (Brown, 2018;Lobell, 2021;Okun, 1999).…”
Section: Building Brave[r] Spacementioning
confidence: 99%
“…The Equity 101 curriculum includes a strong container to make room for brave [r] conversations within a healing, supportive environment (Brown, 2012;Brown, 2018).…”
Section: Assetsmentioning
confidence: 99%
See 1 more Smart Citation